Perbandingan Algoritma Fitness of Spring dan Algoritma Tabu Search pada Kasus Penjadwalan Perkuliahan - Laswi, Aishiyah Saputri (Prodi Teknik Informatika FIK Universitas Muslim Indonesia, 2020)
The compilation of lecture schedules is very important at universities for the continuity of the teaching and learning process of study programs. Such as at Andi Djemma Palopo University, Informatics Engineering Study Program. Frequently occurring alternate lectures to change course schedules is a complex thing considering the pre-existing schedule is well organized. But with the lectures, it is usually difficult to determine schedules, days, hours, rooms, and classes so that, no alternate lectures are coinciding with other subjects. so that in this Case Study, the researcher compared two methods namely the Fitness Method and the Taboo Search Algorithm to see the performance when determining the replacement schedule. The values obtained from the results of the implementation of the two methods above, are with using the fitness method is 40 while for the taboo search the maximum value obtained is 15, based on the order of the schedule of previous courses and courses that will be replaced. Thus, the value obtained by using the taboo search method is in the normal category compared to the changing fitness method. Thus, the researcher can conclude that the value obtained by the taboo search is smaller so that, it is good to be used to determine scheduling.